The professionalization of action sports: Mapping trends and future directions - Thorpe, H.; Dumont, G, (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
This volume is being published at a critical moment in the history and development of action sports. While these activities have undergone rapid growth, commercialization and institutionalization over the past five decades (Booth and Thorpe 2007; Rinehart 2000; Thorpe and Wheaton 2013; Wheaton 2013), the inclusion of surfing, skateboarding, sport climbing and BMX freestyle into the Tokyo 2020 Olympic Games and the ongoing politics regarding the possible future inclusion of other action sports (see Thorpe and Wheaton 2011), mean we are witnessing major structural changes at the global level. These changes are trickling down with considerable implications at national and local levels, and in the everyday lives of action sport participants. As international sports organizations with little understanding of the unique cultural dynamics within action sports seek to incorporate these activities under their own structures for the primary purposes of audience building and wooing corporate sponsors, the axes of power are shifting. While Olympic inclusion brings these issues front and centre, it is important to note that such processes have been underway for many years. Mega action sports events such as the X Games (Thorpe and Wheaton 2017), the increasing involvement of transnational corporations (Thorpe 2014) in tandem with the growth and diversification of locally owned action sports companies (Bouchet, Hillairet, and Bodet 2013), the emergence of mainstream media houses and the multiplication of photographers and filmmakers (e.g. Dumont 2015; Woermann 2012) and the widespread usage of digital technologies (e.g. Dumont 2017a; Thorpe 2017a) have been realtering the flows of resources, knowledge, products and people for many years.